Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/anie.202209659
|View full text |Cite
|
Sign up to set email alerts
|

Core‐Shell ZnO@Microporous Organic Polymer Nanospheres as Enhanced Piezo‐Triboelectric Energy Harvesting Materials

Abstract: Core-shell nanospheres were prepared by the homogeneous coating of piezoelectric ZnO nanorod aggregates with triboelectric microporous organic polymer (MOP). The small energy harvesting performance of ZnO@MOP was significantly enhanced, compared with those of ZnO and MOP, due to the piezoelectrification-induced polarization of inner ZnO and the enhanced generation of tribopositive charges of MOP. Piezo-triboelectric nanogenerators (PTENGs) fabricated with ZnO@MOP showed peak-to-peak voltages of up to 534 V and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…28 In the IR spectrum of MOPN-TZnM, while the main vibration peaks of TZnM were retained at 2993, 1463, 1227, and 1114 cm −1 , new vibration peaks were observed at 1607, 1502, and 825 cm −1 , corresponding to aromatic CC and C–H vibrations originating from the tetra(4-ethynylphenyl)methane building block. 29…”
mentioning
confidence: 99%
“…28 In the IR spectrum of MOPN-TZnM, while the main vibration peaks of TZnM were retained at 2993, 1463, 1227, and 1114 cm −1 , new vibration peaks were observed at 1607, 1502, and 825 cm −1 , corresponding to aromatic CC and C–H vibrations originating from the tetra(4-ethynylphenyl)methane building block. 29…”
mentioning
confidence: 99%
“…Many reports have been proposed to achieve high output performances of TENGs, thus making them suitable for powering a wide range of medical implants. At first, Figure a shows the methods of embedding high dielectric nanoparticle materials into polymer matrices to enhance their surface potential. Seung et al reported a high dielectric nanocomposite material, BTO@P­(VDF-TrFE), composed of barium titanate nanoparticles (BTO) and polyvinylidene fluoride-trifluoroethylene (P­(VDF-TrFE)) . They employed Kelvin probe force microscopy (KPFM) to quantify the surface potential of BTO@P­(VDF-TrFE).…”
Section: Materials Design For High Output Performances Of Self-powere...mentioning
confidence: 99%
“…Typically, at least one of the triboelectric surfaces used in TENG is composed of a polymer material, 83,84 such as polyvinylidene fluoride (PVDF), 85,86 PI, 13,87 nylon, 88,89 polyacrylonitrile, 90,91 and polytetrafluoroethylene 92,93 . Compared to classical metal and inorganic tribo‐materials, polymer tribo‐materials (PTMs) possess various functional groups (–F, –CN, –COOH, and –CONH), which can facilitate charge transfer and capture during the CE process through their unique hybrid orbital configurations 8,94,95 . Furthermore, PTMs also offer numerous advantages, including diverse material selection, excellent flexibility, processability, extensibility, ductility, and lightweight, making them the fundamental building blocks of TENG technology 8,96 …”
Section: Recent Advances In Hto‐tengmentioning
confidence: 99%